A Study of Seasonal and Temporal Variances in Ambient Air Quality of Highly Polluted Cities in Rajasthan - Apoorva Verma; Dr. Leena Bhatia (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The quality of the urban environment in tropical and subtropical densely populated cities is a complicated subject that has garnered a lot of attention in the current setting. Some of the most polluted cities in Rajasthan are Bhiwadi, Jaipur, Kota, and Udaipur, where the air quality has drastically declined over the previous ten years, according to an IQAir report. In order to determine the seasonal and temporal fluctuations in the concentrations of major air pollutants, such as carbon monoxide (CO), ozone (O3), nitrogen dioxide (NO2), sulphur dioxide (SO2), and particulate matter (PM10 and PM2.5), in an urban setting in Rajasthan, this study will examine the ambient air quality in severely polluted cities throughout the state. A comprehensive investigation of the seasonal and temporal variations in ambient air quality throughout Rajasthan’s extremely polluted cities was made possible by the application of PCA and the K-Means Clustering Algorithm. We interpreted the intricate patterns of pollution oscillations by means of rigorous time-series analysis, providing insight into the dynamic interactions among meteorological conditions, sources of pollution, and regulatory actions. The results indicate that there were more seasonal variations during the summer, and that levels of particulate matter (PM10 and PM2.5) and nitrogen dioxide (NO2) in places like Jaipur, Bhiwadi, Kota, and Udaipur alarmingly rose above pre-pandemic levels. This highlights the significance of identifying and addressing the various challenges caused by air pollution at different times of the year and in different seasons. Furthermore, identifying the main sources of pollution and assessing the effectiveness of current legislation offer insightful information for focused actions.